Similarity of introduced plant species to native ones facilitates naturalization, but differences enhance invasion success. Issue 1 (December 2018) - Divíšek, Jan; Chytrý, Milan; Beckage, Brian; Gotelli, Nicholas; Lososová, Zdeňka; Pyšek, Petr; Richardson, David; Molofsky, Jane
Abstract The search for traits associated with plant invasiveness has yielded contradictory results, in part because most previous studies have failed to recognize that different traits are important at different stages along the introduction–naturalization–invasion continuum. Here we show that across six different habitat types in temperate Central Europe, naturalized non-invasive species are functionally similar to native species occurring in the same habitat type, but invasive species are different as they occupy the edge of the plant functional trait space represented in each habitat. This pattern was driven mainly by the greater average height of invasive species. These results suggest that the primary determinant of successful establishment of alien species in resident plant communities is environmental filtering, which is expressed in similar trait distributions. However, to become invasive, established alien species need to be different enough to occupy novel niche space, i.e. the edge of trait space. Plant functional traits may help distinguish introduced species that will become invasive from those that do not. Here, Divíšek et al. show that functional profiles of naturalized plant species are similar to natives, while those of invasive plant species exist at the edge of the functional trait space.